2010
DOI: 10.1055/s-0029-1244080
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy (POEM) for esophageal achalasia

Abstract: The short-term outcome of POEM for achalasia was excellent; further studies on long-term efficacy and on comparison of POEM with other interventional therapies are awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,169
0
45

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,596 publications
(1,227 citation statements)
references
References 16 publications
13
1,169
0
45
Order By: Relevance
“…Inoue H. et al performed the first POEM in adults in 2008. [18] The first pediatric POEM was reported in 2012 for a 3-year-old girl with achalasia and Down's syndrome. The child experienced adequate symptom relief when followed for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue H. et al performed the first POEM in adults in 2008. [18] The first pediatric POEM was reported in 2012 for a 3-year-old girl with achalasia and Down's syndrome. The child experienced adequate symptom relief when followed for 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of the peroral endoscopic myotomy (POEM) procedure by Inoue et al in 2008 provided another means of treatment that has been presented worldwide [40]. Initially described by Pasricha et al [41], this form of natural orifice transluminal endoscopic surgery (NOTES) has provided adequate symptom relief, shown similar shortterm results, and is less invasive as compared to laparoscopic Heller myotomy [42].…”
Section: Treatmentmentioning
confidence: 99%
“…The term POEM was coined by Inoue et al, who initially reported its usefulness in 17 adult patients with achalasia. 19 Since then, many studies have been published that demonstrate excellent short term outcomes and safety of POEM for achalasia. Reported complications include subcutaneous emphysema, mucosal injury, pneumothorax, pneumomediastinum, pleural effusion, and pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%